Improving the quality of hospital care provided to people aged 11–25 years with a mental health condition. (2nd August 2020) - Freeth, Heather; Wood, Sophie; Allsopp, Mark; Wilkinson, Kathy
Abstract : The National Confidential Enquiry into Patient Outcome and Death undertook a detailed analysis of data from 1269 patients aged 11–25 years, admitted to hospital with intentional injury, affective disorder, or eating disorders, to assess the quality of physical and mental healthcare provided. This article summarises the findings and associated recommendations relevant for the general hospital setting.